Sacrococcygeal Teratoma in a Child: A Case Report - Roka, Yam B; Shrestha, Manzil; Pandey, Sagar R (Journal of Nepal Paediatric Society, 2010)
Sacrococcygeal teratomas (SCT) are tumors that arise in the sacrococcygeal area containing tissue from all three germ layers. SCT has an incidence of approximately one in 35,000 – 40,000 live births with malignant transformation with increasing age. We report a case in a four year old which was excised completely via the postanal route with no operative or postoperative morbidity. The histopathology was that of yolk sac variant and she is planned for chemoradiotherapy. Key words: Childhood tumors; Sacrum; Sacrococcygeal teratoma DOI: 10.3126/jnps.v30i2.3450 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 113-115